2019
DOI: 10.5114/wiitm.2019.85464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enhanced recovery protocol with conventional care in patients undergoing minor gynecologic surgery.

Abstract: Introduction: Data regarding the role of the enhanced recovery after surgery (ERAS) protocol in improving postoperative outcomes and postoperative compliance in patients undergoing gynecological surgery, in particular, minor laparoscopic and hysteroscopic gynecological procedures, are limited. Aim: To investigate the impact of the ERAS protocol on time to ambulation, length of stay (LOS), readmissions and postoperative complications in patients undergoing minor gynecological surgical procedures. Material and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…In the ERAS group there is improved quality of life in physical and psychological domains with no difference in social and environmental domains. Similarly, Yoong et level with the ERAS program on the scale of 1 to 10, in patients of vaginal hysterectomy before (n = 50) or after (n = 50) ERAS [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the ERAS group there is improved quality of life in physical and psychological domains with no difference in social and environmental domains. Similarly, Yoong et level with the ERAS program on the scale of 1 to 10, in patients of vaginal hysterectomy before (n = 50) or after (n = 50) ERAS [13].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized trial, Yilmaz et al . 91 aimed to investigate the impact of ERAS in patients undergoing minor gynecological surgical procedures (laparoscopic and hysteroscopic). One hundred and four patients were randomly allocated to one of the following study groups: the ERAS group or the conventional care group, which consisted of age-matched control patients who did not receive ERAS interventions.…”
Section: Enhanced Recovery After Surgery In Minimally Invasive Gynecological Surgerymentioning
confidence: 99%
“…The descriptive characteristics of the included studies are shown in Table 2. Three RCTs [17][18][19] and 24 Non-RCTs were included in this meta-analysis, involving a total of 6344 patients.…”
Section: Characteristics Of the Researchmentioning
confidence: 99%
“…Therefore, subjective factors cannot be completely excluded in the study of ERAS pathways. The three RCTs [17][18][19] included in our meta-analysis referred only to the randomization of patients but did not refer to blinded medical personnel or patients. An RCT design for ERAS pathways study also mentions that medical personnel, patients, and family members will not be blinded in the trial due to the procedures differing between groups and physicians who perform the surgery 54 .…”
Section: Strengths and Limitationsmentioning
confidence: 99%